Development and Evaluation of Garcinia parvifolia (Miq)Miq from Tablet Dosage Forms - Faizatun; Syamsudin (International Journal of Pharma and Bio Sciences, 2010)
Dry and wet methods can be applied for granulation. It is said that final use of prepared granules as tablets dictates the preparation method. At the present study the formulation of the extract of the stem bark of G. parvifolia as tablet dosage form was performewd by use of formulation using dry and wet methods and compared inrespect to characteristics like hardness test, weight uniformity test, friability test, disintegration time and dissolution test and other properties. Results showed that it was concluded that it is better to use wet method for granulation it final aim is produce tablets of the granules. Other wise if the granules will be used as such and there method can be used because of the advantages of this method in respect to low cost of production course, no need to use organic solvents and feasibility in industrial scale production.